Effects of acupuncture and computer-assisted cognitive training for post-stroke attention deficits: study protocol for a randomized controlled trial. Issue 1 (December 2015) - Huang, Jia; McCaskey, Michael; Yang, Shanli; Ye, Haicheng; Tao, Jing; Jiang, Cai; Schuster-Amft, Corina; Balzer, Christian; Ettlin, Thierry; Schupp, Wilfried; Kulke, Hartwig; Chen, Lidian
Abstract Background A majority of stroke survivors present with cognitive impairments. Attention disturbance, which leads to impaired concentration and overall reduced cognitive functions, is strongly associated with stroke. The clinical efficacy of acupuncture with Baihui (GV20) and Shenting (GV24) as well as computer-assisted cognitive training in stroke and post-stroke cognitive impairment have both been demonstrated in previous studies. To date, no systematic comparison of these exists and the potential beneficial effects of a combined application are yet to be examined. The main objective of this pilot study is to evaluate the effects of computer-assisted cognitive training compared to acupuncture on the outcomes of attention assessments. The second objective is to test the effects of a combined cognitive intervention that incorporates computer-assisted cognitive training and acupuncture (ACoTrain). Methods/Design An international multicentre, single-blinded, randomised controlled pilot trial will be conducted. In a 1:1:1 ratio, 60 inpatients with post-stroke cognitive dysfunction will be randomly allocated into either the acupuncture group, the computer-assisted cognitive training group, or the ACoTrain group in addition to their individual rehabilitation programme. The intervention period of this pilot trial will last 4 weeks (30 minutes per day, 5 days per week, Monday to Friday). The primary outcome is the test battery for attentional performance. The secondary outcomes include the Trail Making Test, Test des Deux Barrages, National Institute of Health Stroke Scale, and Modified Barthel Index for assessment of daily life competence, and the EuroQol Questionnaire for health-related quality of life. Discussion This trial mainly focuses on evaluating the effects of computer-assisted cognitive training compared to acupuncture on the outcomes of attention assessments. The results of this pilot trial are expected to provide new insights on how Eastern and Western medicine can complement one another and improve the treatment of cognitive impairments in early stroke rehabilitation. Including patients with different cultural backgrounds allows a more generalisable interpretation of the results but also poses risks of performance bias. Using standardised and well-described assessments, validated for each region, is pivotal to allow pooling of the data. Trial registration Clinical Trails.gov ID:NCT02324959 (8 December 2014)